The Effect of The Effectiveness of The Implementation of Fingerprint Attendance on Work Discipline at PT. Terang Cahaya Abadi Sejati - Azahra, Sayyida; Candra Fatihah , Dian (International Journal of Management and Business, 2024)
The development of science and information technology in the current era of globalization is seen to be increasing very rapidly, so that systems that were once manual are now electronic such as human resource management in terms of taking attendance/attendance of employees at PT. Terang Cahaya Abadi Sejati which uses an electronic attendance system (fingerprint). This study aims to determine the effect of the effectiveness of the implementation of fingerprint attendance in improving employee work discipline. This study uses quantitative research through data collection using questionnaires. The number of samples used was 30 people who were employees at PT. Terang Cahaya Abadi Sejati. The results of this study show that the application of fingerprint attendance has a positive and significant influence on the work discipline of employees of PT. Terang Cahaya Abadi Sejati. This is evidenced by the result of a regression coefficient of positive This is evidenced by the variable X1 (Practical) having a Sig. of 0.000< 0.05 and a calculated t-value of 3.941>2.05183. The obstacles that occurred at PT. Terang Cahaya Abadi Sejati is caused by employees experiencing urgent personal situations, feeling that they are not closely supervised, and lacking a sense of responsibility or commitment to work. The solution that can be given to the Company is to check attendance regularly, ensuring that all employees understand the importance of notifying their absences in the right way. Using an attendance system or time tracker that monitors employee attendance and whereabouts during working hours.